2022
DOI: 10.1523/jneurosci.1458-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Integrins Bidirectionally Regulate the Efficacy of Inhibitory Synaptic Transmission and Control GABAergic Plasticity

Abstract: For many decades, synaptic plasticity was believed to be restricted to excitatory transmission. However, in recent years, this view started to change, and now it is recognized that GABAergic synapses show distinct forms of activity-dependent long-term plasticity, but the underlying mechanisms remain obscure. Herein, we asked whether signaling mediated by b1 or b3 subunit-containing integrins might be involved in regulating the efficacy of GABAergic synapses, including the NMDA receptor-dependent inhibitory lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
3
9
0
Order By: Relevance
“…It is interesting to note that in our recent study Wiera et al, (2022) we found that whereas application of RGD depressed GABAergic transmission recorded from pyramidal neurons, RRETAWA potentiated it. Therefore, whereas observed here effect of RRETAWA in SST + INs was similar to that described in principal cells by Wiera et al, (2022), impact of RGD in PV + and SST + INs tended to be the opposite with respect to that in pyramidal cells 30 . Again, we may attribute these diverging effects to different sets of integrins involved and thereby to different intracellular molecular modulatory pathways.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It is interesting to note that in our recent study Wiera et al, (2022) we found that whereas application of RGD depressed GABAergic transmission recorded from pyramidal neurons, RRETAWA potentiated it. Therefore, whereas observed here effect of RRETAWA in SST + INs was similar to that described in principal cells by Wiera et al, (2022), impact of RGD in PV + and SST + INs tended to be the opposite with respect to that in pyramidal cells 30 . Again, we may attribute these diverging effects to different sets of integrins involved and thereby to different intracellular molecular modulatory pathways.…”
Section: Discussionsupporting
confidence: 90%
“…In an electrophysiological study, Chan et al (2006) have shown that in a model in which β1 integrin was knocked out in forebrain excitatory neurons, an impaired synaptic transmission through AMPA receptors and weakened NMDAR-dependent long-term potentiation were observed 15 . In the context of integrin-dependent modulation of glutamatergic (especially NMDAR-dependent) drive it is worth mentioning that in the present study application of RRETAWA peptide interfering with α5β1 integrins prevented NMDAR-dependent induction of iLTP in SST + INs similar to iLTP in pyramidal cells described in our recent report 30 . It may be hypothesized that this effect of integrins on iLTP might be, at least in part, due to their action on NMDARs.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations